Intranets: A New Dimension for Library Services - Bhojaraju, G. (DESIDOC Journal of Library & Information Technology, 2003)
This article is based on the some practical experiences of Indian Rubber Manufacturing Research Association (IRMRA). It gives brief introduction about the intranet, controversies of an intranet, and its library applications. It also gives information about accessing management information, improving internal communications, e-mail, intra mail, collaborative working, communities of interests, discussion groups, electronic forms, internal newsletters, search facilities, training materials, and library applications/access. The use of intranet in providing library services like SDI, CAS and other information management is explained with a schematic diagram. http://dx.doi.org/10.14429/dbit.24.1.3617